CrkII Transgene Induces Atypical Mammary Gland Development and Tumorigenesis - Fathers, Kelly E. (American Society for Investigative Pathology, 2010)
The v-Crk protein was originally isolated as the oncogene fusion product of the CT10 chicken retrovirus. Cellular homologues of v-Crk include Crk, which encodes two alternatively spliced proteins (CrkI and CrkII), and CrkL. Though CrkI/II proteins are elevated in several types of cancer, including breast, the question of whether these Crk adaptor proteins can promote breast cancer has not been addressed. We created a transgenic mouse model that allows the expression of CrkII through the hormonally responsive mouse mammary tumor virus promoter. During puberty, transgenic mice were found to have delayed ductal outgrowth, characterized by increased collagen surrounding the terminal end buds. In post-pubertal mice, precocious ductal branching was observed and associated with increased proliferation. Focal mammary tumors appeared in a subset of animals, with a latency of approximately 15 months. Mouse mammary tumor virus/CrkII tumors showed high levels of Crk protein as well as various cytokeratin markers characteristic of their respective tumor pathologies. This study demonstrates that the precise expression of CrkII is critical for integrating signals for ductal outgrowth and branching morphogenesis during mammary gland development. Furthermore, this study provides evidence for a potential role of CrkII in integrating signals for breast cancer progression in vivo, which has important implications for elevated CrkII observed in human cancer.